Pengaruh Manajemen Mutu Farmasi Terhadap Peningkatan Mutu Pelayanan Rumah Sakit Umum Rajawali Citra Bantul Yogyakarta - Susyana Candra Santi Dewi (Jurnal Indonesia Sehat, 2022)
Background: Hospitals are labor-intensive, capital-intensive, technology-intensive and skills-intensive organizations. The demands of progress which require the improvement of all aspects of the Hospital in the context of providing quality services, make the problems in the Hospital even more complex. Hospital service quality dimensions (ServQual) consist of (1). Reliability (reliability), (2). Assurance (3), physical evidence (tangible), (4) empathy, and (5) responsiveness. Hospital pharmacy services are one of the activities in hospitals that support quality health services. This is clarified in the Decree of the Minister of Health Number 1333/Menkes/SK/XII/1999 concerning Hospital Service Standards, which states that hospital pharmacy services are an integral part of the hospital health service system. Method: This research is a quantitative descriptive study with a cross sectional design, because it is a research that seeks or obtains independent (free) and dependent (bound) variables which are carried out at the same time.  Result: Data were analyzed with validity and reliability tests for each questionnaire item, with valid and reliable results. For processing and analysis of research data using multiple regression analysis, t test and f test. The independent variable in this study is quality management which includes reliability, responsiveness, assurance, empathy and tangibles, while the dependent variable is service quality improvement (Y). The known regression equation is: Y = 0.191 + 0.159 X1 + 0.129 X2 + 0.199 X3 + 0.227 X4 + 0.138 X5. The results of a significance of 0.000 < 0.05 or (p ) < ?, indicate that simultaneously or partially the independent variable has an influence on the dependent variable, and hypothesis testing with the F test is obtained: for the calculated F value is 25.141> F table is 2.330 while the coefficient the determination (R2) is 0.614. Conclusion: This study is that there is a significant influence of pharmaceutical quality management on service quality improvement of 61.4%, and the hospital should prioritize the quality of service for optimal satisfaction results.